Az Ideológia és utópia hajótörése: Mannheim Károly Ideológia és utópia című műve német és angol változatának összevetése - Bognár, Virág (Szociológiai Szemle, 2024)
In the literature on Mannheim basically two views are current on how the differences between the German and English variants of Ideology and Utopia can be interpreted: a) the sociology of knowledge has undergone a basic theoretical change, b) the English variant is an organic continuation of the German original. The present paper gives a different answer. It attempts to eliminate the ’shortcomings’ of earlier literature by relying among others on the ’list of differences’ of more than one hundred pages between the two textual variants, prepared by the author. One should not see the radically changed theory of the sociology of knowledge in the English variant, neither some kind of ’organic’ continuation of the original theory, but such a version in which some of the stylistic elements of thinking in the German original have disappeared and the remaining ones have been mixed with new ones; they create ambivalence and tension instead of creating a similar, or radically different reading experience in the reader. With such an open editing of the text, which characterises almost all of Mannheim’s writing, he apparently ’stands out’ of the line of theoreticians. The origin of the new elements is of two kinds: Mannheim wished to incorporate the original theory of interpretation into a general theoretical framework of sociology (of knowlendge). Its most important consequence was the separation of interpretation by the sociology of knowledge from understanding. It is impossible to extend the broadening of rationalisation so mich that it should swallow even the sphere of the irrational. On the other hand the experience of the victory of fascism and the sence of the approaching war had the greatest influence upon the changes of theory: it became obvious that the sociology of knowledge was unable to say anything worthwhile about authority, as it was too exposed in the face of it. The paper tries to avoid ’labelling’ and strives to interpret Mannheim’s theory in its constant change.